The Digitalization of Investment Impact on Developing Tourism Industry - Julianti, Lis; Pinpak, Artit (Lembaga Contrarius Indonesia, 2024)
Digitalization of investment can boost the development of the tourism sector. However, regulations in Indonesia related to digital investment still need to be improved, thus triggering risks for investors. This research aims to analyze the impact of digitalization of investment on the development of the tourism sector. This research uses normative legal study with a conceptual, legislative, and comparative approach. The research results show that, first, investment digitalization impacts the development of the tourism sector. However, various problems still need to be solved, including suboptimal regulations, overlapping authorities, digital gaps between regions, and a need for more privacy data protection. Second, investment digitalization in Japan and Thailand has several advantages compared to Indonesia, mainly due to more advanced technological infrastructure, strategic government policies, and a more mature digital economy. Third, Indonesia must implement the principle of legal certainty and protection by strengthening investment digitalization regulations and collaborating with various parties to prepare special regulations regarding investment digitalization and increase data privacy protection to realize sustainable tourism and development.